2012
DOI: 10.20886/jped.2012.6.2.141-154
|View full text |Cite
|
Sign up to set email alerts
|

KAJIAN EKOLOGI Parashorea malaanonan MERR DI HUTAN PENELITIAN LABANAN KABUPATEN BERAU, KALIMANTAN TIMUR

Abstract: ABSTRAKParashorea malaanonan (Blco) Merr. merupakan salah satu spesies dari famili dipterokarpa dari marga Parashorea yang sudah terancam punah. Parashorea malaanonan (Blco) Merr. sudah masuk dalam daftar IUCN dengan status critically endangered, sehingga perlu dilakukan suatu penelitian mengenai kondisi ekologinya di hutan alam agar ke depannya jenis ini memiliki data yang lengkap tidak hanya data taksonomi dan penyebarannya, tapi juga informasi mengenai kondisi ekologi habitatnya, sehingga informasi mengenai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…According to Ruchaemi (2013), the optimal temperature for vegetation is between 25 and 30 °C to carry out the photosynthesis process. High and low air temperatures can impede vegetation growth and lead to death (Fajri & Saridan, 2012). Mangrove and pine forests, on the other hand, have high air temperatures and low humidity due to the lack of canopy cover over the forest floor.…”
Section: The Effect Of Environmental Factors On Increasing the Carbon...mentioning
confidence: 99%
“…According to Ruchaemi (2013), the optimal temperature for vegetation is between 25 and 30 °C to carry out the photosynthesis process. High and low air temperatures can impede vegetation growth and lead to death (Fajri & Saridan, 2012). Mangrove and pine forests, on the other hand, have high air temperatures and low humidity due to the lack of canopy cover over the forest floor.…”
Section: The Effect Of Environmental Factors On Increasing the Carbon...mentioning
confidence: 99%
“…A study by Yuliana (2012) found that soil with low pH content can jeopardise the growth of plants since it reduces the availability of essential nutrients. However, Fajri & Saridan (2012), who conducted research in Labanan forest, East Kalimantan, stated that soil pH was not a single factor in determining plant growth. They argued that the Al 3+ level also affected the condition.…”
Section: Soil Propertiesmentioning
confidence: 99%